Associations between cardiorespiratory fitness, motor competence, and adiposity in children. Issue 1 (28th September 2020) - Haapala, Eero A.; Gao, Ying; Lintu, Niina; Väistö, Juuso; Vanhala, Anssi; Tompuri, Tuomo; Lakka, Timo A.; Finni, Taija
Abstract: We investigated the associations of motor competence (MC) with peak oxygen uptake (V̇O2peak ), peak power output (Wmax ), and body fat percentage (BF%) and whether measures of cardiorespiratory fitness (CRF) modify the associations between MC and BF%. Altogether, 35 children (aged 7‐11 years) in the CHIPASE Study and 297 in PANIC Study (aged 9‐11 years) participated in the study. MC was assessed using KTK and modified Eurofit tests. V̇O2peak and Wmax were measured by maximal exercise test on a cycle ergometer and scaled by lean mass (LM) or body mass (BM). BF% was assessed either by bioimpedance (CHIPASE) or DXA (PANIC). MC was not associated with V̇O2peak /LM (standardized regression coefficient β  = 0.073‐0.188, P  > .083). V̇O2peak /BM and Wmax /LM and BM were positively associated with MC ( β  = 0.158‐0.610, P  < .05). MC ( β  = −0.186 to −0.665, P  < .01), but not V̇O2peak /LM ( β  = −0.169‐0.035, P  > .381), was inversely associated with BF%. Furthermore, the associations of MC with BF% were not modified by CRF. These results suggest that the positive associations between MC and CRF scaled by BM are a function of adiposity and not peak aerobic power and that CRF is not modifying factor in the associations of MC and BF%.